2022
DOI: 10.1080/10717544.2022.2036870
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of berberine erythrocyte-hemoglobin self-assembly delivery system: a neglected carrier underlying its pharmacokinetics

Abstract: Berberine (BBR) has extremely low concentration and high tissue distribution. However, current pharmacokinetic studies predominantly focus on its concentration in plasma, which could hardly make a comprehensive understanding of its pharmacokinetic process. This study made a pioneering endeavor to explore the erythrocyte-hemoglobin (Hb) self-assembly system of BBR by exploring the interaction of BBR with erythrocyte and the combination of BBR with Hb. Results showed that BBR had a low bioavailability ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“… 26 In our previous work, a BBR erythrocytes-Hb self-assembly delivery system has been identified and the accumulation of BBR in erythrocytes was attributed to the intense conjugation of BBR with Hb. 12 In this study, BBR achieved a significantly higher concentration in erythrocytes than in plasma in rats after intragastrical administration with PCC and intraperitoneal administration with BBR, which was in agreement with our previous findings. 12 , 13 HCl, a hydrolyzing agent, could be used for the hydrolysis of drug-Hb adducts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 26 In our previous work, a BBR erythrocytes-Hb self-assembly delivery system has been identified and the accumulation of BBR in erythrocytes was attributed to the intense conjugation of BBR with Hb. 12 In this study, BBR achieved a significantly higher concentration in erythrocytes than in plasma in rats after intragastrical administration with PCC and intraperitoneal administration with BBR, which was in agreement with our previous findings. 12 , 13 HCl, a hydrolyzing agent, could be used for the hydrolysis of drug-Hb adducts.…”
Section: Discussionsupporting
confidence: 93%
“… 24 Erythrocytes harbor various distinctive properties such as unmatched long circulation, biocompatibility and biodegradability that make them appealing vascular carriers for in vivo delivery of natural and synthetic payloads. 9 , 25 Although our previous study has suggested a BBR erythrocytes-Hb self-assembly delivery system, 12 the metabolic aspect, targeted delivery and dose–effect relationship of BBR mediated by erythrocytes have not yet been clearly clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After Genetic Algorithm was used for the calculating, the Autodock program was run for the second docking operation [ 29 ]. The binding energy was calculated and successful docking was defined by a binding energy of ≤ -5 kJ/mol [ 30 ]. Figures of the selected binding sites were generated using PyMOL software…”
Section: Methodsmentioning
confidence: 99%
“…In an animal study in rats, berberine (2.5 mg/kg) was administered intravenously and C 0 was 2.833 μg/ml and when a dose of 400 mg/kg berberine was administered orally in rats, Cmax was 0.260 μg/ml. AUC 0−t was also found to be low in both mentioned routes of administration (Yu et al, 2022).…”
Section: Pharmacokinetic Parametersmentioning
confidence: 97%